2009
DOI: 10.1086/596498
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Seasonality, Age Distribution, and Mortality of Pneumococcal Meningitis in Burkina Faso and Togo

Abstract: Streptococcus pneumoniae causes a substantial proportion of meningitis cases in the African meningitis belt; however, few reports exist to quantify its burden and characteristics. We conducted population-based and sentinel hospital surveillance of acute bacterial meningitis among persons of all ages in Burkina Faso and Togo in 2002-2006. S. pneumoniae and other organisms were identified by culture, polymerase chain reaction, or detection of antigen in cerebrospinal fluid (CSF). Information was collected on 284… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 20 publications
8
54
3
3
Order By: Relevance
“…As the initial aim of this method is to provide a cost-effective alternative to conventional serotyping in resource-poor regions with minimal or no vaccine coverage, the identifiable serotypes are still likely to be common in pneumococcal disease and carriage in these regions (5,41,42,61). Strains with ambiguous sequetype results and those without an amplicon can be assessed by conventional serological and other DNA-based methods, most likely targeting the wzy and wzx regions (35).…”
Section: Discussionmentioning
confidence: 99%
“…As the initial aim of this method is to provide a cost-effective alternative to conventional serotyping in resource-poor regions with minimal or no vaccine coverage, the identifiable serotypes are still likely to be common in pneumococcal disease and carriage in these regions (5,41,42,61). Strains with ambiguous sequetype results and those without an amplicon can be assessed by conventional serological and other DNA-based methods, most likely targeting the wzy and wzx regions (35).…”
Section: Discussionmentioning
confidence: 99%
“…S. agalactiae, also known as group B Streptococcus (GBS) is the main microbial agent responsible for serious infections in newborns [15] . In Burkina Faso few studies have been done on the genus, in particular Streptococcus pneumoniae but no prevalence study has been done on the GBS [16,17] . In this study, GBS is ranked third among the microorganisms responsible for vaginosis, with prevalence around 10%.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate the need for the development of immunization programs, especially in poor countries, to reduce morbidity and mortality (273). Surveillance studies of serotypes causing invasive pneumococcal disease in developing countries have also demonstrated that the current 7-valent pneumococcal vaccine would not cover all serotypes causing invasive disease and have suggested that wider coverage would be provided by the 10-valent or 13-valent pneumococcal conjugate vaccines (13,17,22,98,173,221,267,273,283,307,351,354). The introduction of these vaccines into these vulnerable populations is a crucial, but expensive, step to control this serious infection.…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%